Study On Normal Stresses In Composite Curved Beams Subjected To Unsymmetrical Bending - Yu, Aimin (Engineering Transactions, 2002)
Based on the formula for normal stresses in curved beams of one material, the formulae for normal stresses in composite curved beams with general cross-sectional shape under complicated loads can be derived. The novel formulae presented in this paper can be used in evaluating the normal stresses of connecting rod bush coated with bearing metal for internal combustion engine. These normal stress formulae, in special case, are reduced to those for composite curved beams subjected to symmetrical bending. A numerical example is given for verification at the end of this paper.